Social Transformations and Political Empowerment in the Age of Globalization: Looking beyond Women's Empowerment in Tanzania (Nordic Journal of African Studies, 2003)
The paper reviews the efforts attempted so far to create a social movement for political empowerment of women in post-independence Tanzania. It locates the various women groups within the larger social context and analyzes the role gender plays in intra-household resource allocation and the mechanisms which maintains the prevailing structure of social relations. Firstly, the paper assesses the organizational resources which have been available to women and how these have facilitated the creation of a movement. The tutelage of women by men as fathers, uncles, brothers, and husbands is seen as a major impingement on independent resource management by women. Increased workload on women due to technological change in economic production is also highlighted. The sedentarisation of pastoralists and the resulting degradation of rangelands are shown to have changed women's property rights in livestock; to have made it possible for men to redefine women's traditional rights and consolidate control both over livestock and dairy incomes. The political opportunity structure under which women have been operating in Tanzania is, however, seen as fairly favourable to women empowerment. The paper sees women in Tanzania as the vanguards of the struggle for the second liberation, which is the agenda for this millennium.